Pengembangan Perangkat Pembelajaran Matematika Berbasis Discovery Learning Untuk Meningkatkan Kemampuan Penalaran Matematis Peserta Didik Kelas VIII SMP/MTS - R.Iska Meiliputri; Hendra Syarifuddin; Edwin Musdi; Ali Asmar (JEMS: Jurnal Edukasi Matematika dan Sains, 2021)
Learning tools are important things used in the learning process. The use of this learning device has a major effect on the ability of students, one of which is the ability of mathematical reasoning. Learning tools in the form of RPP and LKPD can form effective learning and make it easier for teachers and students in learning. Based on this, it is necessary to develop learning tools that are expected to help students develop mathematical abilities, especially mathematical reasoning abilities. One thing that can help students and teachers is to develop discovery learning-based learning tools to improve students' mathematical reasoning abilities. The purpose of writing this article is to develop a valid, practical, and effective learning tool for the mathematical reasoning abilities of students in class VIII in junior high school by using the discovery learning model. This type of research is development research using the Plomp model. The Plomp model consists of an initial investigation stage, a prototype development stage, and an assessment stage. The research subjects were students of class VIII. The results showed that: (1) The learning tools in the form of RPP and LKPD based on discovery learning were valid in terms of content and constructs. (2) Practical because it is easy to use and understand, the allocated time is very efficient, interesting and contributes to learning. (3) From the results of the mathematical reasoning test, it shows that the discovery learning-based learning device has been effective in improving mathematical reasoning seen from the results of the final test carried out on students.